Potential of optical coherence tomography and intravascular ultrasound in the detection of vulnerable plaques in coronary arteries - N. A. Kochergin; A. M. Kochergina (Кардиоваскулярная терапия и профилактика)
Intravascular imaging of vulnerable plaques in vivo has great potential for predicting coronary events. Currently, there are several methods of intravascular imaging, which make it possible to verify the components of the plaque and, accordingly, its vulnerability. The most common are virtual-histology intravascular ultrasound and optical coherence tomography. Several studies have shown that these imaging techniques can stratify the risk of adverse cardiovascular events, as well as assess the effectiveness of drug therapy. This article will describe the advantages and disadvantages of intravascular ultrasound and optical coherence tomography in identifying vulnerable coronary lesions.